Strategi Public Relations dalam Mendukung Pemasaran Pembangkit Listrik Nasional (PLN) - Novi Anggraeni; Mukarto Siswoyo; Farida Nurfalah (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2014)
Public relations is one of the elements that determine the viability of an organization positively. The purpose of the research; 1). Knowing the planning public relations strategies in support of marketing; 2). Knowing the kinds of public relations activities; 3). Knowing the packaging contents of the message of the communication media used; 4). Knowing the effect to be achieved; and 5). Knowing the obstacles faced. The method used descriptive qualitative. Results of the study are: 1. Judging from the background criteria for Public Relations of PT. PLN (Persero) APJ Cirebon is formal education, job experience, appearance, skills, individual characteristics, and adaptation, credible communicator. 2. Kegiatan Public Relations to support the marketing of which the existence of a local radio talk show in Cirebon (Cirebon FM), a local television talk show in Cirebon (RCTV), cooperation in carrying out tasks related to corporate law. 3. Packaging persuasive message content, preparation of informative messages are intended to provide excitement and build consumer understanding. 4. The effect achieved a change in opinions, attitudes and behavior. 5. Barriers found limited use of communication media and the lack of communication superiors and subordinates